Characterization of nuclear proteins that bind the EFII enhancer sequence in the Rous sarcoma virus long terminal repeat. - Sears, R C (1992)
The EFII cis element is a 38-bp sequence at the 5' end of the Rous sarcoma virus long terminal repeat, extending from nucleotides -229 to -192 (with respect to the viral transcription start site), which is recognized by sequence-specific DNA-binding proteins in avian fibroblast nuclear extracts (L. Sealy and R. Chalkley, Mol. Cell. Biol. 7:787-798, 1987). We demonstrate that multiple copies of the EFII cis element strongly activate transcription of a reporter gene in vivo. We correlate the region of the EFII cis element which activates transcription in vivo with the in vitro binding site for three nuclear factors, EFIIa, EFIIb, and EFIIc. The sequence motif recognized by EFIIa, -b, and -c is also found in consensus binding sites for members of a rapidly growing family of transcription factors related to the CCAAT/enhancer-binding protein (C/EBP). EFIIa, -b, and -c are present in fibroblast and epithelial cell lines from various species but are much less abundant in differentiated rat liver and kidney cells. The EFIIa binding activity is particularly abundant in an avian B-cell lymphoma line. As judged from molecular weight analysis, cell type distribution, and sequence recognition properties, the EFII factors under study appear to differ from most of the previously described C/EBP-related factors and thus may expand the diversity of the C/EBP family.